Alinaya Fabros. Outsourceable Selves: An Ethnography of Call Center Work in a Global Economy of Signs and Selves. Quezon City: Ateneo de Manila University Press, 2016, 292 pp. - Gappy, John Martin Bernard (Archīum Ateneo, 2018)
Excerpt: The Philippines is well known for exporting skilled labor worldwide through its ‘Overseas Filipino Workers’ program but in 1997 a new form of Filipino workers emerged within the country: call center agents. Call centers offer full time jobs as well as above-average compensation to highly educated Filipinos with the advantage of staying in the country. Without migrating, the well-educated youth could now afford a middle-class, ‘cosmopolitan’ lifestyle in the emerging new cities with their luxurious condominiums. Where businesses are concerned, cheaper labor costs in South East Asia allow worldwide corporations to cut on costs and offer greater profits to their shareholders. In Outsourceable Selves: An Ethnography of Call Center Work in a Global Economy of Signs and Selves, the author discusses the work relationships between conglomerates and call center agents, channeled through the local call center agencies. She exposes several work practices within the workplace that affect call center employees physically, psychologically, socially and culturally.